Agriculture, Food Systems, and Sustainable Development in Asia: Challenges and Pathways - Hamed Kioumarsi (Journal of Biotropical Research and Nature Technology, 2025)
This review analyzes different aspects of agriculture, food systems, and sustainable development in Asia, a geographically variable, economically booming, and ecologically very diverse continent. The review considers progress as well as regional systems regarding sustainable development, organic crop, and livestock farming systems along with cropping. It also addresses the consequences of climate change on fish and aquaculture, the control of soil and carbon sequestration, and the effects on the availability of food. Further, the review discusses microbial science in supporting the development of sustainable and resilient food systems, food diversity and quality, while also critically examining the challenges and gains of implementing sustainable agriculture. Asian countries are confronting important development challenges and need to move toward sustainable and resilient food systems immediately. While significant progress has been achieved in reducing poverty, ensuring food security, and modernizing agricultural, numerous challenges still remain, including the impacts of climate change, environmental degradation, loss of biodiversity, and malnutrition. The prevailing production-focused models of input intensification as well as linear resource use cannot adequately address these interlinked challenges. Sustainable agriculture and food systems in Asia can be achieved through a multi-dimensional strategy. This would include developing and instituting policy systems that make green and inclusive practice more effective, prioritizing the benefits to the smallholder farmer. Technology and social innovation, such as upscaling climate-smart agriculture, digitalization, and knowledge-sharing mechanisms, are essential for enhancing productivity and resilience. Promoting regional and global cooperation through cross-border association, emergency funds, and knowledge transfer mechanisms is essential in order to mitigate shocks and stimulate development. Also essential are strategic public and private investments to modernize infrastructure, support research programs, and grant vulnerable populations autonomy. Ultimately, an overall approach that fosters cooperation between governments and people is essential for propelling sustainable food and agriculture systems towards a more resilient world.